2012
DOI: 10.3390/ijerph9124522
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hypertension and Chronic Arsenic Exposure in Drinking Water: A Cross-Sectional Study in Bangladesh

Abstract: Chronic arsenic exposure and its association with hypertension in adults are inconclusive and this cross-sectional study investigated the association. The study was conducted between January and July 2009 among 1,004 participants from 1,682 eligible women and men aged ≥30 years living in rural Bangladesh who had continuously consumed arsenic-contaminated drinking water for at least 6 months. Hypertension was defined as systolic blood pressure ≥140 mmHg (systolic hypertension) and diastolic blood pressure ≥90 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…In this analysis, we assumed both a constant log-linear (log-transformed water As concentration) and a flexible non-linear (restricted cubic splines with knots at the 10th, 50th and 90th percentiles of log-transformed water As concentration) associations. The median value was assigned as the concentration level for each concentration category and if the median value was not provided directly, the mean or the midpoint values were calculated instead [16,25,45,59,63,[66][67][68][69][70][71][72][73][74][75]. For the calculation of the midpoint value for each concentration category, zero was used as the minimum if not available [16,25,66,[68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis, we assumed both a constant log-linear (log-transformed water As concentration) and a flexible non-linear (restricted cubic splines with knots at the 10th, 50th and 90th percentiles of log-transformed water As concentration) associations. The median value was assigned as the concentration level for each concentration category and if the median value was not provided directly, the mean or the midpoint values were calculated instead [16,25,45,59,63,[66][67][68][69][70][71][72][73][74][75]. For the calculation of the midpoint value for each concentration category, zero was used as the minimum if not available [16,25,66,[68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have associated high-level of arsenic exposure from drinking water with elevated risk of vascular diseases, including peripheral vascular disease, hypertension, ischemic heart disease and carotid atherosclerosis [6]. Epidemiological studies reported increased incidence of hypertension in arsenic-exposed populations [7][8][9]. Further, evidences showed that arsenic induced hypertension in rats [10,11] and mice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted on a Bangladesh population had demonstrated increased occurrence of hypertension, diabetes mellitus, and chronic respiratory disorders in terms of chronic cough and asthma among arsenicosis patients compared to those having no exposure to arsenic [17][18][19][62][63][64][65]. Studies revealed (Table 2-7) that the crude prevalence ratio for diabetes mellitus among arsenicosis patients was 4.4 (95%, CI 2.5-7.7).…”
Section: Suspected Case Showing Melanosis or Keratosis After Excludinmentioning
confidence: 99%